An Ordinance Relating to Guns, Pistols, and Other Weapons, in The Pioneer Democrat, Jun. 11, 1887, at 2. - (:unkn) unknown (My University, 1887)
That is shall be unlawful for any person or persons to come inside the corporate limits of this city with any gun, pistol, or weapon of any kind on his person or in his possession or charge. Provided, however, that the marshal or his deputy may permit any person or persons who is in his opinion should be permitted to pass through said city with their guns, pistols or other weapons, so to do.
Keywords: POSSESSION